PENGARUH SISTEM PENGENDALIAN INTERN, SISTEM AKUNTANSI KEUANGAN DAERAH DAN KAPASITAS SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN, STUDI PADA PEMERINTAH DAERAH KABUPATEN SLEMAN: PENGARUH SISTEM PENGENDALIAN INTERN, SISTEM AKUNTANSI KEUANGAN DAERAH DAN KAPASITAS SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN, STUDI PADA PEMERINTAH DAERAH KABUPATEN SLEMAN - Assari, Indri Dian; Binawati, Enita (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2022)
This study aims to determine the effect of the internal control system, regional financial accounting system and human resource capacity on the quality of local government financial reports in Sleman Regency. The population in this study is the subdivision of finance, accountants (bookkeepers) and treasurers (receipts and expenditures) of the Sleman Regency Regional Apparatus. This study used 118 respondents. Data were obtained by distributing questionnaires. Using quantitative descriptive analysis method. Data analysis used multiple linear regression with a significant level of 5%. The results showed that, simultaneously, the variables of the internal control system, regional financial accounting system and human resource capacity had a significant positive effect on the of the quality of local government financial reports, as evidenced by the results of the simultaneous test (F test). Partially, the internal control system variables affect the quality performance of local government financial reports, and the regional financial accounting system variables and human resource capacity also affect the quality of local government financial reports, this is evidenced by the results of the partial test (t test)